Moral Altruis dalam Filsafat Sosial Perspektif Perbandingan dengan Akhlak dalam Islam dan Pengaruhnya terhadap Ekonomi - Djakfar, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2004)
The term Altruist moral can be corresponded with al-akhlaq al-mahmudah (good moral). The word "altruist" derives from "altruistic" (English) which means a character that emphasizes on other needs. Therefore, someone with altruist moral can be called as a person who has a character that emphasizes on other needs. Globalization era which is dominated by rapid development of information and technology has carried out an enormous changes to the life of society in many factors, including economic. Recently, many people have begun to question again about competence as well as moral role and ability to manage and control moral of society that becomes more permissive, not submissive anymore as occurred in the past. Analysis result says that whether in social philosophy or Islam, Altruist moral will deliver economic attitude which orients to do the obligation first, than asking for the right to its own necessity (individual egoist - annaniyah). Altruist moral, referred to Yusuf Qardhawi, will widely give effect on the whole aspect of economy, whether in the case of production, consumption, circulation or distribution.